(untitled) (Italian Review of Legal History, 2024)
The constitution Super speculam, promulgated in 1219 by Pope Honorius III, is a very important text in the history of university teaching. Taken in application of the Fourth Lateran Council (1215), it primarily concerns the teaching of theology, of which the University of Paris is the centre, but also law. Wishing to promote the teaching of theology, Honorius III renewed the old prohibitions on regular clerics studying the law and extended them to many categories of secular clerics. To this important general context must be added a more specifically Parisian one. The criticism that theologians had long levelled at jurists, who were accused of attracting more and more students, was intensifying. The conflicts that developed between the masters and the chancellor from 1210 onwards, particularly the one that pitted them against Philip the Chancellor in spring 1219, fostered this antagonism between jurists and theologians. Influenced by the theologians, Honorius III banned the teaching of Roman law in Paris and the surrounding areas, at the end of Super speculam.